Supplementary oxygen efficacy for chronic pulmonary disorders and exertion desaturation - Paraschos Archontakis Barakakis; Adam Wolfe; Andrei Schwartz; Gabriel J. Hernandez Romero; Vipul Gidwani; Shaylika Chauhan; Shinichi Arizono; Ralph J. Panos; Spyridon Fortis (ERJ Open Research)
Introduction Exertion-induced desaturation (EID) is a common complication of numerous pulmonary disorders and often treated with supplementary oxygen during exertion. We performed a systematic review and meta-analysis of randomised clinical trials (RCTs) to evaluate the efficacy of supplementary oxygen for EID in pulmonary disorders. Material and methods Medline and Embase were systematically searched from July 2022 to June 2023 following PRISMA guidelines. RCTs that met predefined inclusion criteria were included. Means and standard deviations were extracted and standardised mean differences (SMDs), the difference in means between groups divided by the standard deviation, and 95% confidence intervals were calculated. Exercise capacity was the primary outcome; exercise dyspnoea, baseline dyspnoea and quality of life were secondary objectives. The immediate, post-rehabilitation, short-term and ambulatory effects of oxygen supplementation were evaluated. Results We included 15 studies in our analysis. Oxygen supplementation to treat adult EID had been investigated for COPD and idiopathic pulmonary fibrosis (IPF) only. Oxygen supplementation was superior to placebo for its immediate effect on exercise capacity for COPD (SMD 0.42, 95% CI 0.15–0.69, I2=3%) and IPF (SMD 0.41, 95% CI 0.08–0.75, I2=57%) and exercise dyspnoea for COPD (SMD −0.40, 95% CI −0.76–−0.04, I2=31%). Sensitivity analysis revealed similar results. Conclusions Our study revealed the efficacy of supplemental oxygen for EID and only a positive immediate effect on exercise capacity and dyspnoea, but no improvement in other short-term or long-term measures.